De la justicia transicional: verdades y mentiras sobre la paz en Colombia. El inicio de la violencia (2017)
The historic pass for a state like Colombia has not been easy; because once we got independence and converted into a republic, society spent nine wars that marked the nineteenth century; came the twentieth century and the conflicts between party ideologies entailed to uprisings in arms, who later would rise to the “rabble” and the chulavitas; the first was a group of liberal farmers, motivated by passions overwhelmed after bogotazo and second, a legal armed group, made up of conservative peasants from the village chulavita in Boyacá, whose task was to eradicate violence in Bogotá generated by the rabble: mission who developed blood and fire effectively, through massacres. After removing the legality of the above structure, not all members of these groups CARRY OUT dereliction of weapons, following his own act; this is why: they are branded paramilitaries in Colombia precursors (Pecaut, 2011). The chusmeros mutate peasant self-defense groups and later on socialist guerrillas; to combat these, the estate would throw hand back to the figure of legal self-defense, which, would be dismantled within its framework only of legality by the end of the twentieth century and to close the period, enter the scene is drug trafficking, enhancer of violence in the country.